Mathematics
hayhay12
29

simplify the following expression 3(2x+5)-4x+2

+2
(2) Answers
Muddymoy

Hello --- okay so write the eqation on your paper. 3(2x+5)-4+2 Distributive Property 1st! So take the 3 and do 3*2x and 3*5.  It should look like this... 6x+15-4+2 After that you can add 15 and 2 6x+17-4 17-4= 13 YOUR ANSWER= 6x+13. You can't combine 6x and 13 because 6x has a X and 13 doesn't! Hope that helped! -Brittany

KayIseman

3 ( 2x + 5 ) - 4x + 2 Distributive property 3 * 2x = 6x 3 * 5 = 15 6x + 15 - 4x + 2   combine like terms 6x - 4x = 2x 15 + 2 = 17 2x + 17 will be the final answer:)

Add answer